Dressing up : menswear in the age of social media - Bluteau, Joshua M. (New York : Berghahn Books, 2022)
"What does men's fashion say about contemporary masculinity? How do these notions operate in an increasingly digitized world? To answer these questions, author Joshua M. Bluteau combines theoretical analysis with vibrant narrative, exploring men's fashion in the online world of social media as well as the offline worlds of retail, production, and the catwalk. Is it time to reassess notions of masculinity? How do we construct ourselves in the online world, and what are the dangers of doing so? From the ateliers of London to the digital landscape of Instagram, Dressing Up re-examines the ways men dress, and the ways men post"--
Includes bibliographical references and index.
Keywords: Men's clothing -- Social aspects; Social media -- Influence; Fashion merchandising; Masculinity